MEMBACA IDENTITAS ETNIK DALAM SINEMA INDONESIA KINI - Murfianti, Fitri (Capture : Jurnal Seni Media Rekam, 2009)
Principally, a film is a product of recorded media in which a socio-cultural identity included. It is multi function. People or viewers via film find as a mirror to look at the social, cultural, political and economical dynamic of their life. In one side , film seems just a canalization of their life. But the other side film appears as an escapism of an individual of man from the fluctuation of life. Nevertheless, a film can be a reflection that society also reflect the way of life. It is alike newspapers, films hopefully to be a medium of showing things to construct the idea and power.Keyword : etnik identity, Indonesia cinema